EFIKASI DIRI TERHADAP KINERJA MENGAJAR GURU SMA - Rahmawati, Ima; Ihsan, Muzhir; Mukri, Rusdiono; Rinawati (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
Teacher teaching performance is the result of the teacher's work carried out during the learning process which includes planning, implementation and evaluation of learning outcomes. The purpose of this research is to determine the influence of self-efficacy on teacher teaching performance. This research used a quantitative approach with an associative method involving 54 high school teachers in Tenjolaya District as respondents who were taken using non-probability sampling with a saturated sample. Data is collected primarily using a closed questionnaire or questionnaire using a Likert scale with 5 answer options (SL, SR, KD, P, TP), then the data is processed using inferential statistikal techniques which include classic assumption tests and hypothesis testing to determine the influence and how big it is. The influence of teacher teaching performance variables on self-efficacy variables. The research results show that self-efficacy has a positive and significant effect on the teaching performance of high school teachers in Tenjolaya District with a contribution of 43.5%. This means that teacher teaching performance can be improved through self-efficacy.